2012
DOI: 10.1258/jtt.2012.gth101
|View full text |Cite
|
Sign up to set email alerts
|

The costs and potential savings of telemedicine for acute care neonatal consultation: preliminary findings

Abstract: Telemedicine was used as a substitute for the telephone (usual care) for some acute care consultations from nurseries at four peripheral hospitals in Queensland. Over a 12-month study period, there were 19 cases of neonatal teleconsultation. Five (26%) cases of avoided infant transport were confirmed by independent assessment, four of which were avoided helicopter retrievals. We conducted two analyses. In the first, the actual costs of providing telemedicine at the study sites were compared with the actual sav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 3 publications
4
27
0
2
Order By: Relevance
“…These positive impacts of telemedicine on avoiding unnecessary transports and cost savings have been consistently found among published reports, including evaluations done internationally. 27,161,162 Intensive Care…”
Section: Telemedicine In the Intensive Care Settingmentioning
confidence: 99%
“…These positive impacts of telemedicine on avoiding unnecessary transports and cost savings have been consistently found among published reports, including evaluations done internationally. 27,161,162 Intensive Care…”
Section: Telemedicine In the Intensive Care Settingmentioning
confidence: 99%
“…7 In a second study, 5 of 19 neonates who underwent tele-consultation avoided transport, and as a result use of telemedicine was associated with substantial cost savings. 20 Overall, clinicians report having a positive impression of telemedicine for neonatal consultation. 8 There have been more limited studies of telemedicine use for subspecialty evaluation of neonates, and they have generally focused on image interpretation and not performance of a full subspecialty physical examination.…”
Section: Discussionmentioning
confidence: 99%
“…7, 8, 19, 20 A recent study comparing bedside and telemedicine neonatologist evaluations of 46 neonates found excellent or intermediate-to-good agreements for almost all components of the evaluation. However, poor agreement was identified for several physical examination features including auditory components (breath, cardiac, bowel sounds) and capillary refill time.…”
Section: Discussionmentioning
confidence: 99%
“…Telemedicine applications in the intensive care unit (ICU) have been designed to improve quality of care and access to health care, especially for those who live in remote or underserved areas. The importance of telemedicine in general neonatal care has been reported as improving patient outcomes, communication, accessibility, and reducing cost of care . In a comparison of actual costs of neonatal telemedicine with actual savings associated with confirmed avoided infant aeromedical transport and nursery costs, there were net savings to the health system of 54,400 AUD (Australian Dollars), which were associated with the use of neonatal telemedicine over a period of 12 months .…”
Section: Introductionmentioning
confidence: 99%
“…The importance of telemedicine in general neonatal care has been reported as improving patient outcomes, communication, accessibility, and reducing cost of care . In a comparison of actual costs of neonatal telemedicine with actual savings associated with confirmed avoided infant aeromedical transport and nursery costs, there were net savings to the health system of 54,400 AUD (Australian Dollars), which were associated with the use of neonatal telemedicine over a period of 12 months . Utilization of telemedicine has also proved to reduce the number of low birth weight deliveries in hospitals without NICUs, and reduce statewide infant mortality .…”
Section: Introductionmentioning
confidence: 99%